2017
DOI: 10.1039/c7lc00646b
|View full text |Cite
|
Sign up to set email alerts
|

“Open-top” microfluidic device for in vitro three-dimensional capillary beds

Abstract: We introduce a novel microfluidic device to co-culture a blood vessel network and cell tissues in an in vivo-like niche. Our "open-top" microfluidic device is composed of microchannels with micropores in the ceiling, which provides direct fluid access from reservoir to microchannel. Fluid connections through micropores afford novel advantages, including: i) the long-term culture of large-scale microvessel network, ii) access of different fluids to inner and exterior sides of the microvessel, and iii) co-cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 44 publications
0
61
0
1
Order By: Relevance
“…S1A). The device was designed similarly to recently published methods ( 27, 28 ), but with modifications that (A) promoted maintenance of the air-liquid interface between the central channel and adjacent media channels, and (B) allowed for loading of cells and hydrogel precursors into a previously wetted channel. Essential to this approach is the ability to wet the central channel during the differentiation of hMSCs while keeping the adjacent media channels dry throughout the process so that a second set of cells can be loaded within the central channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A). The device was designed similarly to recently published methods ( 27, 28 ), but with modifications that (A) promoted maintenance of the air-liquid interface between the central channel and adjacent media channels, and (B) allowed for loading of cells and hydrogel precursors into a previously wetted channel. Essential to this approach is the ability to wet the central channel during the differentiation of hMSCs while keeping the adjacent media channels dry throughout the process so that a second set of cells can be loaded within the central channel.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several groups have published methods for in vitro vasculogenesis in similar microfluidic platforms ( 27, 28, 33, 34 ). We found that perfusion of the vasculature was most consistent using a combination of hMSCs in laterally adjacent channels, supplementation with vascular endothelial growth factor (VEGF) and angiopoietin-1 (ANG-1), and encapsulation of endothelial cells in a fibrin/collagen co-gel ( Error!…”
Section: Resultsmentioning
confidence: 99%
“…A similar chip design was used for investigating the effects of physical cues on sprouting; in this case, interstitial flow was generated that promoted sprouting against the direction of the flow [21]. These type of systems have also been used in the research on tumour vasculature and the effect of different drugs on the vasculature and tumour progression [75][76][77][78][79].…”
Section: Angiogenesis-based Platformsmentioning
confidence: 99%
“…Open microfluidic systems are characterized by the introduction of an air-liquid interface, where liquid flows in microscale channels devoid of at least one side-wall (2,5,6,13). Unlike typical microfluidic devices with enclosed culture chambers, open devices offer increased pipette accessibility at any point along the culture chamber and simpler fabrication processes, such as straightforward micro-milling and injection molding, allowing open microfluidic devices to become efficient tools with versatility and transferability across different research disciplines (11,18,30,31,40,49,58).…”
Section: Open Microfluidic Device Design and Workflowmentioning
confidence: 99%